Insect diversity and succession pattern on different carrion types - Kyerematen, Rosina AK; Boateng, Bernard A; Twumasi, Emmanuel (Journal of Research in Biology, 2012)
Insect fauna attracted on four different types of carrion; beef, chicken, pork, and fish were conducted in a cassava growing field on the campus of the University of Ghana for a period of twenty-eight days between February and March, 2005. Four stages of decomposition were recognized; fresh, bloated, decay and dry. A total of 19 insect species belonging to five orders and thirteen families were recorded. Coleoptera represented 23% of the total number of species. Diptera and Hymenoptera constituted 35% and 41% respectively while Collembola and Heteroptera a mere 1% of the insect orders that dominated the carrion fauna. Caliphoridae were the first to arrive on all four types of carrion. Five species of Histeridae, three of Formicidae and one each from Dermestidae, Scarabaeidae, Cleridae, Mycetophagidae, Scolytidae were recorded on beef, chicken, pork and fish. Representatives of four Dipteran families; Calliphoridae, Muscidae, Sarcophagidae and Tachinidae were also recorded. One species each of the families Pyrrhocoridae and Isotomidae were unique to pork and chicken respectively.